2-AFC for Detectability of Low Contrast Object of CT Images Scanned with Two Doses and Recontructed with Various Iterative Recontruction (IR) Levels (International Journal of Scientific Research in Science and Technology, 2024)
This study aims to evaluate images of the low contrast and small objects of the American Association of Physicists in Medicine (APPM) computed tomography (CT) phantom scanned with two doses and reconstructed with various iterative reconstruction (IR) using the 2-alternative forced choice (2-AFC) method. A module 610-06 of the APPM CT phantom had been scanned with a GE Revolution Apex CT scanner. The module was scanned with two difference radiation doses of 40.8 mGy and 57 mGy. The images were reconstructed with various IR levels of 0, 20, 40, 60, 80, and 100%. Detection of the low contrast object (i..e. 10 HU difference) with size of 3 mm was performed using the 2-AFC. The question bank has a total of 120 questions, with each type of data has 10 questions. This study involved 6 medical personnel having experience periods of less than three years (3 people) and more than three years (3 people). It is found that percent correct increases with increasing IR level and radiation dose. 100% correct at a dose of 40.8 mGy occurs at an IR level of 100%. Meanwhile, 100% correct at a dose of 57 mGy occurs at an IR level of 40%. Expert medical personnel who have worked for more than three years have a greater percent correct than medical personnel who have worked for less than three years. A study using 2-AFC on low contrast detectability for various IR level and two different doses has been performed. It was found that IR level and radiation dose increase detectability of the low contrast object.